GaN Improves Efficiency of an Asymmetrical Half-Bridge PWM Converter with Synchronous Rectifier - Kohlhepp, Benedikt; Barwig, Markus; Dürbaum, Thomas (PCIM Europe 2019; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, 2019)
As the asymmetrical half-bridge PWM converter achieves high efficiency by employing zero voltage switching (ZVS), it is a highly promising candidate for switch mode power supplies. Nevertheless, high efficiency in low output voltage applications requires synchronous rectification. Even though a simple replacement of the Schottky rfectifier diode by a synchronous rectifier shows promising results by simulation, practical setups reveal great deviations. Strong damped oscillations during turn-off of the synchronous rectifier induce enormous losses. Using a GaN-FET as synchronous rectifier featuring its very good parasitic properties solves the problem during turn-off. Therefore, this paper analyzes an asymmetrical half-bridge PWM converter design employing a GaN-HEMT as synchronous rectifier, directly focusing on solving the identified proble